Didactic strategies to strengthen chemical language in education - Elizeth Mayrene Flores Hinostroza; Derling Jose Mendoza Velazco; Lorena Soledad Revilla; Karina Maribel Castillo Pinos (Indonesian Institute for Counseling, Education and Theraphy, 2022)
The objective of the research article presented below was to propose activities that would strengthen the students of the educational institution